The Relationship between Body Balance and Futsal Ball Dribbling Skills in State Junior High School 3, South Bengkulu - Jaka Putra; Mesterjon, Mesterjon; Perdima, Feby Elra (Journal of Physical Education and Sports, 2025)
Body balance as one of the components of basic motor skills that are very much needed in mastering basic futsal technical skills, especially dribbling. This study aims to determine the relationship between body balance and futsal ball dribbling skills in students who are members of the futsal extracurricular at State Junior High School 3 Bengkulu Selatan. This study uses a quantitative approach with a correlational method. The subjects of the study were 26 students who were members of the futsal extracurricular. Data collection techniques were carried out through body balance tests (holding time in a certain position) and dribbling skills tests (measuring the time to complete dribbling obstacles). The data obtained were analyzed using descriptive statistics and the Pearson Product Moment correlation test. The results of the analysis showed that students' body balance had an average value of 31.86 seconds, with most students in the "sufficient" and "good" categories. Meanwhile, dribbling skills showed an average travel time of 16.36 seconds, with the dominant category distribution in "sufficient" and "good". The results of the correlation test showed that there was a very strong and significant relationship between body balance and dribbling skills, with a correlation coefficient value of 0.952 and a significance of 0.000 (p <0.01). This finding indicates that body balance plays an important role in supporting dribbling skills in futsal. Therefore, the development of balance skills needs to be given attention in physical and technical training programs in the school environment. This study provides practical contributions for PJOK teachers, extracurricular coaches, and further researchers in designing sports coaching based on the development of basic motor skills.